+0  
 
0
127
2
avatar

solve=  - 2z + 3 + 7 z = -12

Guest Apr 26, 2017
Sort: 

2+0 Answers

 #1
avatar
0

have NO clue u need help

Guest Apr 26, 2017
edited by Guest  Apr 26, 2017
 #2
avatar+4786 
+2

 -2z + 3 + 7z = -12

 

Combine like terms.

5z + 3 = -12

 

Subtract 3 from both sides of the equation.

5z = -12 - 3

5z = -15

 

Divide both sides of the equation by 5.

z = -15/5

z = -3

hectictar  Apr 26, 2017

7 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details